2019
DOI: 10.1155/2019/4634823
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hypertension in a Typical State-Level Poverty-Stricken County in China and Evaluation of a Whole Population Health Prevention Project Intervention

Abstract: Background. In China, there were 584 state-level, poverty-stricken counties until January 2019. The central government has invested a large amount of funds and preferential policies to alleviate poverty in these areas. The Whole Population Preventive Healthcare Pilot Project (WPPHCPP) aims to explore the use of limited funds to achieve healthy poverty alleviation through free regular physical examinations and comprehensive health management for the entire population in impoverished regions. Objective. By demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Second, to develop decentralized strategies for the care and diagnosis of hypertension cases and to actively involve the community. Evidence suggests active involvement of local communities improves the outcomes of hypertensive patient management and their control of hypertension [ 43 ]. Third, establish a surveillance system to identify people with hypertension and send them regular reminders (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Second, to develop decentralized strategies for the care and diagnosis of hypertension cases and to actively involve the community. Evidence suggests active involvement of local communities improves the outcomes of hypertensive patient management and their control of hypertension [ 43 ]. Third, establish a surveillance system to identify people with hypertension and send them regular reminders (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [3] conducted in Shandong, China in 2011 showed that the empty nesters have a higher non-use rate of healthcare services than non-empty ones due to the fact that the higher demand for health services cannot be met equally, but another study conducted in Sinan county, China, in 2018 was inconsistent with it, which found that the empty nesters were less likely to choose self-treatment. After the 'healthy China 2030' plan released by the central government in 2016, a series of health poverty alleviation projects were implemented with the goal of strengthening financial risk protection against illness for the financially backward population [23][24][25].…”
Section: Discussionmentioning
confidence: 99%